Evaluation of the Outcome of Interventions for Thoracic Endometriosis Syndrome at a Tertiary Level Health Institution in Southern Nigeria - , Christian Emeka Amadi; , Justina Omoikhefe Alegbeleye (Archives of Current Research International, 2024)
Background: Thoracic Endometriosis Syndrome (TES) is a clinical condition characterized by the presence of endometrial tissue within the thoracic cavity, catamenial pneumothorax, catamenial haemothorax, catamenial haemopneumothorax, catamenial haemoptysis and or endometrial nodular lung mass. The management can be challenging as treatment is fraught with recurrence. Aim: To evaluate the outcome of interventions for Thoracic Endometriosis Syndrome. Methods: This was a prospective cross-sectional study of 14 patients with thoracic endometriosis syndrome who were managed at the university of Port Harcourt Teaching Hospital between August 1, 2017, and July 31, 2023. A proforma was used to collect data on socio-demographic characteristics, clinical presentation, type of intervention and evidence of recurrence of chest symptoms and entered into a spread sheet. Data analysis was done with SPSS version 28. Results are presented as frequency tables and percentages. Results: The age of the patients ranged between 20 and 44 years. Of the 14 patients, 11 (78.6%) were married, and 3 (21.4%) of the patients had established abdominal endometriosis with symptoms of thoracic endometriosis, while 4 (28.6%) had a histologic diagnosis of thoracic endometriosis. Pneumothorax was observed in 9 (64.23%) patients, 3 (21.43%) had haemopneumothorax, 2 (14.29%) with cyclical haemoptysis and haemothorax, and 4 (28.57%) of the patients had thoracic endometriotic nodules, while all the married patients had primary infertility. Twelve (85.7%) of the patients had closed tube thoracostomy drainage (CTTD) with chemical pleurodesis, while 4 (28.6%) had thoracotomy, decortication, bleb, and nodules resection with chemical pleurodesis. All the patients had hormonal therapy using luteinizing hormone-releasing hormone (LHRH) analogues. There was recurrence in 2 (14.3%) of the patients after a one-to-six-year period of follow-up. Conclusion: The treatment of TES using CTTD with pleurodesis, thoracostomy, decortication, bleb resection and or hormonal therapy with appropriate patient selection is effective as only two cases of recurrences were recorded.